2018
DOI: 10.3390/molecules23040869
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarin Mitigates Aβ-Induced Neurotoxicity and Improves Behavior Impairments in AD Mice

Abstract: Alzheimer’s disease (AD) is pathologically characterized by excessive accumulation of amyloid-beta (Aβ) within extracellular spaces of the brain. Aggregation of Aβ has been shown to trigger oxidative stress, inflammation, and neurotoxicity resulting in cognitive dysfunction. In this study, we use models of cerebral Aβ amyloidosis to investigate anti-amyloidogenic effects of scutellarin in vitro and in vivo. Our results show that scutellarin, through binding to Aβ42, efficiently inhibits oligomerization as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…Therefore, the PC12 cell line was used for the therapeutic evaluation of Scue. Similar to previous studies, 2 µg/ml Aβ induced ~32% cell death, whereas, pretreatment with Scue inhibited Aβ-induced apoptosis (9,38), thus, demonstrating that Scue may protect against the pro-apoptotic cellular effects of Aβ in vitro .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, the PC12 cell line was used for the therapeutic evaluation of Scue. Similar to previous studies, 2 µg/ml Aβ induced ~32% cell death, whereas, pretreatment with Scue inhibited Aβ-induced apoptosis (9,38), thus, demonstrating that Scue may protect against the pro-apoptotic cellular effects of Aβ in vitro .…”
Section: Discussionsupporting
confidence: 88%
“…The flavonoid compound scutellarin (Scu) is ubiquitous in nature, particularly in the genus Erigeron (Asteraceae) and Scutellaria (Lamiaceae), and has been widely used in traditional Chinese medicine for a number of millennia (911). Recently, studies have made significant progress assessing the benefits of Scu, which exhibited neuroprotective effects, including anti-oxidant, anti-inflammatory and anti-apoptotic activities in numerous diseases (12–14).…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's is the most common cause of dementia, accounts for 80% of cases, which leads to the progressive loss of cognitive skills, mental abilities, and learning capability (Anand et al, 2014;Zeng et al, 2018). Altering APP proteolysis is the most obvious feature of Alzheimer's, which produces abnormal Ab to induce neurotoxic effects; soluble Ab oligomerization is strongly correlated with cognitive decline in AD patients (Kim et al, 2013).…”
Section: Figmentioning
confidence: 99%
“…Inflammation in the brain is one of the hallmarks of AD and is initiated in the central nervous system (Zeng et al, 2018). Numerous studies have reported that Aβ can trigger oxidative stress in the brain, and also activate microglia leading to neuroinflammation and cognitive dysfunction (Kobayashi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%